Flipbook-Based Digital E-book Learning Media on Mechanical Wave Materials to Practice Critical Thinking Skills - Izmi Afifatul Azizah; Imam Sucahyo (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
The research aimed to know the validity, practicality, and effectiveness of e-book learning media on learning to train students' higher-order thinking skills. The research method used is the type of quantitative research. The research was carried out by giving a pretest, then being treated, and then a posttest. The subjects of this study were students of class XI Saince 2 Senior High School NU 1 Gresik. Data collection techniques using pretest-posttest and questionnaires. Data analysis used validity test, Cronbach alpha reliability test, and t-test. The results of the research that have been processed and analyzed can be concluded that the flipbook-based e-book learning media has an average validation value of 85.066%, categorized as very valid. Learning media has a practicality value of 85.067%, included in the very practical category. The questionnaire is classified as accurate because of the importance of rcount > rtable and is categorized as reliable because it has an alpha value of 0.869. Through the t-test, the significance value of 0.000 is less than 0.05, meaning there is a significant effect in giving treatment. Therefore, the research can be concluded that the flipbook-based digital e-book learning media obtains a valid category, is suitable for use, and trains students' critical thinking skills.